Teaching Wisdom and Virtue: The Educational Legacy Of Jami and Navoi’s Epics On Alexander - Otayarova Umida Bolibek Qizi (Web of Scientist International Scientific Research Journal, 2025)
This study explores the moral and educational legacy of two prominent Eastern literary figures—Abdurahman Jami and Alisher Navoi—through their epics Khiradnomayi Iskandariy and Saddi Iskandariy. The primary aim is to examine how these works instill virtues such as generosity, contentment, justice, and moral responsibility in readers, especially within a pedagogical context. Utilizing comparative literary analysis and thematic interpretation, the research investigates the ethical messages conveyed through allegories, fables, and narrative episodes involving Alexander the Great. Methodologically, the study analyzes selected stories from both authors to illustrate their philosophical and didactic intentions. For instance, Jami uses Sufi allegory to emphasize contentment and spiritual wealth, while Navoi presents realistic scenarios to illustrate the practical benefits of generosity and virtue. One notable example is Navoi’s tale of a merchant who unknowingly redeems his lost son through an act of selfless giving. The results highlight that both poets, despite stylistic differences, converge in their portrayal of moral excellence as the foundation of human fulfillment. These works serve not only as literary masterpieces but also as enduring educational resources that promote ethical development. Their relevance persists in modern times, offering valuable lessons in moral conduct and spiritual growth